CONSIDERAȚII PRIVIND DREPTUL PACIENȚILOR DE ALEGERE ÎNTRE TRATAMENTELE ALOPATE ȘI HOMEOPATE. REGIMUL JURIDIC AL MEDICAMENTELOR HOMEOPATE ÎN UNIUNEA EUROPEANĂ (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
Considerations Regarding the Right of Patients to Choose Between Allopatic and Homeopathic Therapies. The Regulatory Framework of Homeopathic Medicines in the European Union.Specific EU legislation for homeopathic medicines has deep roots in their widespread use in member states. Even before the introduction of the first EU legislation in 1992, homeopathic medicines were prescribed and used in all Member States. Regulation of these products dates back to 1967 in France and 1976 in Germany. Directive 92/73/EEC created specific provisions for  homeopathic medicines, aiming to encourage free trade within the  Community and patients’ freedom of choice. In this context, this article  examines how to regulate homeopathic medicines at EU level to ensure the  same high level of quality and safety as other medicines, while recognizing  the importance of national traditions. At the same time, the article aims to  analyze the state of implementation of European legislation at the level of the  member states, taking into account the fact that, based on article 16  paragraph (2), they have the competence to keep or introduce specific rules  for preclinical tests (tests pharmacological and toxicological) and clinical  trials, in accordance with the principles and characteristics of homeopathy  practiced in the respective Member State.